2014
DOI: 10.1039/c4cc00091a
|View full text |Cite
|
Sign up to set email alerts
|

Organelle-selective fluorescent Cu2+ion probes: revealing the endoplasmic reticulum as a reservoir for Cu-overloading

Abstract: Two novel Cu(2+) sensors, 1 and 2, bearing naphthalimide and a DPA moiety were synthesized to study copper accumulation in organelles by selective Cu(2+) sensing. The ER-selective Cu(2+) sensor 1 that we developed serves as a valuable tool for understanding the subcellular compartmentalization and roles of copper ions in physiology and pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(44 citation statements)
references
References 46 publications
0
42
0
2
Order By: Relevance
“…S2) [47]. This value is within those (10 3~1 0 12 ) previously reported for Cu 2+ -binding chemosensors [48][49][50][51][52][53]. Based on the result of UV-vis titration, the detection limit for 1-Cu 2+ complex was determined to be 2.4 µM on basis of 3σ/K (Fig.…”
Section: Colorimetric and Spectral Response Of 1 Toward Cu 2+mentioning
confidence: 88%
“…S2) [47]. This value is within those (10 3~1 0 12 ) previously reported for Cu 2+ -binding chemosensors [48][49][50][51][52][53]. Based on the result of UV-vis titration, the detection limit for 1-Cu 2+ complex was determined to be 2.4 µM on basis of 3σ/K (Fig.…”
Section: Colorimetric and Spectral Response Of 1 Toward Cu 2+mentioning
confidence: 88%
“…[75] Another recent study showed that depending on the substitution pattern, amphipathic naphthalimide derivatives can localize either to lysosomes or to the ER ( Figure 4A). [76] Themore hydrophilic naphthalimide-derived probes localized to lysosomes,a nd the more hydrophobic naphthalimide derivatives localized to the ER with high selectivity.W er ecently demonstrated that implementing the organelle-targeting approach can improve the performance of azole antifungal drugs. [77] Members of the azole class of antifungal drugs are the first-line treatment for invasive fungal infections.…”
Section: Targeting the Endoplasmic Reticulum And Golgi Apparatusmentioning
confidence: 99%
“…140 Chou et al reported a BODIPY based CHEF system, where the careful matching of the molecular orbital energy of BODIPY and a Cu 2+ selective selenoether resulted in a off-on fluorophore (29, Fig. 144 32a and 32b were shown to localise preferably in the ER and the lysosomes, respectively (by co-localisation experiments) when HepG2 cells are incubated with the dyes. The fluorophore was used to visualise the copper overloading process in RAW264.7 cells.…”
Section: View Article Onlinementioning
confidence: 99%
“…12). 144 As HepG2 cells are a liver carcinoma cell line, these results could be significant to the progression of WD and might be an important consideration in the design of WD drugs. 141 Using 7-nitrobenz-2-oxa-1,3-diazole as a fluorophore and a bis-pyrazole bearing Cu 2+ chelator (30, Fig.…”
Section: View Article Onlinementioning
confidence: 99%